Removal of liquid scintillator exudates by the metal organic frameworks materials: The role of functional groups. - Jie Ren; Peng Wang; Aotian Gu; Chunhui Gong; Kaiwei Chen; Ping Mao; Yan Jiao; Kai Chen; Yi Yang (PLoS ONE)
The leakage of Liquid scintillator exudates has brought potential harm to the environment. Attributed to the large specific surface area and high modifiability, high-performance adsorbents based on metal-organic frameworks (MOFs) can effectively remove organic pollutants. In this work, we use different functional groups to prepare the material of UIO-66(Zr). These materials were used to remove dimethyl sulfoxide (DMSO) from water, which is considered a typical liquid scintillator exudate. The results showed that the UIO-66-NH2 (154.3 mg/g) exhibited better adsorption performance compared to the UIO-66-OH (39.5 mg/g) and UIO-66-COOH (105.8 mg/g) for the removal of DMSO. Upon examining the adsorptive abilities of various samples of different UIO-66-NH2 samples, it was observed that the material's ability to adsorb is in a direct relationship with the -NH2 group concentration present in the substance, as evidenced by a correlation coefficient R2 of 0.99. Simultaneously, in the low concentration of environment, the samples of UIO-66 which load NH2 groups shows high removal effectiveness of over 90%. The adsorption capacity of the prepared materials was little affected by the complex water quality conditions and different initial pH values (between 4~10). Furthermore, the material has good reusability and adsorption capacity over five cycles, and slight zirconium release (< 5%). This optimal material showed significant removal capacity for DMSO. In conclusion, this work presents insight into the construction of advanced adsorbents for the removal of liquid scintillator exudates that have high adsorption capacity and strong potential for DMSO removal.